Structural and Functional Brain Abnormalities Associated With Exposure to Different Childhood Trauma Subtypes: A Systematic Review of Neuroimaging Findings - Cassiers, Laura L. M.; Sabbe, Bernard G. C.; Schmaal, Lianne; Veltman, Dick J.; Penninx, Brenda W. J. H.; Van Den Eede, Filip (Frontiers in Psychiatry, 2018)
Background: Childhood trauma subtypes sexual abuse, physical abuse, emotional maltreatment and neglect may have differential effects on the brain that persist into adulthood. A systematic review of neuroimaging findings supporting these differential effects is as yet lacking. Methods: A systematic literature search was performed using the PubMed and PsycINFO databases. Eligible papers were assessed in greater detail and considered relevant if they reported on controlled neuroimaging trials investigating subtype-specific trauma effects. Results: The systematic literature search yielded 25 publications. Sexual abuse was associated with structural deficits in the reward circuit and genitosensory cortex and amygdalar hyperreactivity during sad autobiographic memory recall. Emotional maltreatment correlated with abnormalities in fronto-limbic socioemotional networks. In neglected individuals, white matter integrity and connectivity were disturbed in several brain networks involved in a variety of functions. Other abnormalities, such as reduced frontal cortical volume, were common to all maltreatment types. Conclusions: There is some evidence for differential effects of trauma subtypes. The observed alterations may result from both protective adaptation of and damage to the brain following exposure to threatening life events. Though promising, the current evidence is incomplete, with few brain regions having been investigated in all subtypes. Future neuroimaging studies should take this potentially differential role of childhood trauma subtypes into account.